The contribution of F.D. Maurice to the Christian Socialist Movement of 1848-1954 - Steel, Ronald Luke (Rhodes University, Faculty of Divinity, Department of Divinity, 1971)
Maurice was a man who solicited both keen support and bitter opposition, both during his life time and after. It is only within the last twenty or thirty years that his true worth has begun to be recognised and appreciated. The aim of the thesis is to show that his contribution to the Christian Socialist Movement was an invaluable one. Chapter two describes the working-class conditions and their causes during the first half of the nineteenth century, as well as the role the Church played in social improvement. Chapter three deals with Chartism and the European Revolutions of 1848, and the effect of the Revolutions on Chartism. Chapter four gives an account of the man F.D. Maurice, as well as some of his thoughts and aims. Chapter five is a detailed account of Maurice's contribution to Christian Socialism, showing that he was not the 'practical' leader, and emphasising the importance of his theological beliefs in governing what to do. Intro. p. 1.
Keywords: Maurice, Frederick Denison, 1805-1872; Christian Socialist Movement